Tin(II) Selective PVC Membrane Electrode Based on Salicylaldehyde Thiosemicarbazone as an Ionophore - Sulekh Chandra; Kusum Sharma; Adarsh Kumar (Journal of Chemistry)
A polymeric membrane-based tin selective electrode was developed by using salicylaldehyde thiosemicarbazone (STSC). The best performance was recorded with a membrane composition of PVC : TBP : ionophore : NaTPB as 28 : 59 : 8 : 5 (w/w%). The Nernstian slope calculated from the calibration curve for Sn2+ sensor was 28.8 ± 0.4 mV/decade. The detection limit of the sensor was 2.10 × 10−8 M, in the linear concentration range of 1.0 × 10−2−1.1 × 10−7 M. It was relatively fast response time (<8 s for concentration ≥1.0×10−4 and <12 s for concentration of ≥1.0×10−6 M) and can be used for 9 months without any considerable divergence in potentials. The proposed sensor exhibit relatively good selectivity and high sensitivity for tin(II) as other mono-, di-, and trivalent cations and can be used in a pH range of 2.0–8.5. The analytical usefulness of the proposed electrode has been evaluated by its application in the determination of stannous in artificially made samples.